2006
DOI: 10.1097/01.wnr.0000220130.86349.a7
|View full text |Cite
|
Sign up to set email alerts
|

Space re-exploration in hemispatial neglect

Abstract: Exploration of the space around us is a fundamental part of human behaviour. When it breaks down there is an important opportunity to understand its underlying mechanisms. Here we show that many right-hemisphere patients with left neglect re-explore rightward locations, failing to keep track of them during search. Importantly, such re-exploration occurred despite leftward stimuli being indistinguishable in peripheral vision, so it is unlikely to result from implicit processing of neglected targets. Revisits ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 16 publications
4
79
0
1
Order By: Relevance
“…Karnath analyzed exploration of a large space by eye and head movements adopting magnetic transducers placed on the eye and on the head [39]. Parton proposed an exploration task on a touchscreen for studying the re-exploration of already touched items which may be alternatively simply tagged, cancelled or enhanced [40].…”
Section: Introductionmentioning
confidence: 99%
“…Karnath analyzed exploration of a large space by eye and head movements adopting magnetic transducers placed on the eye and on the head [39]. Parton proposed an exploration task on a touchscreen for studying the re-exploration of already touched items which may be alternatively simply tagged, cancelled or enhanced [40].…”
Section: Introductionmentioning
confidence: 99%
“…Re-exploration behavior in neglect has often been related to spatial working memory impairment (e.g., Husain et al, 2001;Mannan et al, 2005;Parton et al, 2006;Wojciulik, Husain, Clarke, & Driver, 2001). However, in these studies, no direct evaluation of spatial working memory was carried out, since it was the recancellation behavior itself that was considered as a measure of impaired spatial working memory.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several recent studies of neglect patients required subjects to remember sequentially presented locations arrayed in a vertical line. The results showed that neglect patients had impaired spatial WM performance (Malhotra, Mannan, Driver, and Husain, 2004; Malhotra et al, 2005; Parton, Malhotra, Nachev, Ames, Ball, Chataway, and Husain, 2006). When the eye-movements of neglect patients were assessed in visual search tasks, it was shown that they tend to revisit previously foveated items as if they were new items, indicative of a spatial WM impairment (Husain et al, 2001; Wojciulik, Husain, Clarke, and Driver, 2001).…”
Section: Working Memory For Spatial Attributesmentioning
confidence: 97%